BROCCOLI AND MASTOPATHY: THERAPEUTIC APPLICATION AND POTENTIAL ADVERSE EFFECTS - Khaydarov D.B (Modern American Journals, 2025)
Mastopathy is a non-cancerous condition of the mammary glands, typically arising from hormonal imbalances, and is especially prevalent among women over the age of 30. Treatment generally involves a combination of hormonal therapy, dietary modifications, and natural remedies. In recent years, cruciferous vegetables such as broccoli have gained attention due to their bioactive phytochemicals that may support hormonal health. However, the same compounds can pose risks in certain physiological contexts, prompting a need for cautious evaluation.